Attenuation of Theiler's murine encephalomyelitis virus by modifications of the oligopyrimidine/AUG tandem, a host-dependent translational cis element. - Pilipenko, E V (1995)
A set of Theiler's murine encephalomyelitis virus mutants with engineered alterations in the conserved oligopyrimidine/AUG tandem (E. V. Pilipenko, A. P. Gmyl, S. V. Maslova, G. A. Belov, A. N. Sinyakov, M. Huang, T. D. K. Brown, and V. I. Agol, J. Mol. Biol. 241:398-414, 1994) were assayed for their growth potential in BHK-21 cells (as reflected in plaque size) and for neurovirulence upon intracerebral inoculation of mice. Tandem-destroying mutations, which included substitutions in the oligopyrimidine moiety and extended insertions into the oligopyrimidine/AUG spacer, exerted relatively little effect on the plaque size but ensured a high level of attenuation. The attenuated mutants exhibited remarkable genetic stability upon growth in BHK-21 cells. However, the brains of rare animals that developed symptoms after the inoculation with high doses of these mutants invariably contained pseudorevertants with the oligopyrimidine/AUG tandem restored by diverse deletions or an AUG-generating point mutation. The AUG moiety of the tandem in the revertant genomes was represented by either a cryptic codon or initiator codon. The results demonstrate that the tandem, while dispensable for the Theiler's murine encephalomyelitis virus growth in BHK-21 cells, is essential for neurovirulence in mice. Thus, the oligopyrimidine/AUG tandem is a host-dependent cis-acting control element that may be essential for virus replication under certain conditions. The functional activity of the tandem was retained when its oligopyrimidine or AUG moieties were made double stranded. A possible role of the tandem in the cap-independent internal initiation of translation on the picornavirus RNA templates is discussed.